Human postures modeling using motion analysis: A review - Sazali, Yaacob, Prof. Dr.; Ku Nor Syamimi, Ku Ismail; Murugappan, Muthusamy, Dr.; Shafriza Nisha, Basah, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/